Advances in the Structural and Physiological Functions of SHARPIN - Yu, Beiming; Wang, Feng; Wang, Yanfeng (Frontiers in Immunology, 2022)
SHARPIN was initially found as a SHANK-associated protein. SHARPIN can be used as an important component to form the linear ubiquitin chain assembly complex (LUBAC) with HOIL-1L, HOIP to produce a linear ubiquitin chain connected N-terminal Met1, playing a critical role in various cellular processes including NF-κB signaling, inflammation, embryogenesis and apoptosis. SHARPIN alone can also participate in many critical physiological activities and cause various disorders such as chronic dermatitis, tumor, and Alzheimer’s disease. Mice with spontaneous autosomal recessive mutations in the SHARPIN protein mainly exhibit chronic dermatitis and immunodeficiency with elevated IgM. Additionally, SHARPIN alone also plays a key role in various cellular events, such as B cells activation and platelet aggregation. Structural studies of the SHARPIN or LUBAC have been reported continuously, advancing our understanding of it at the molecular level. However, the full-length structure of the SHARPIN or LUBAC was lagging, and the molecular mechanism underlying these physiological processes is also unclear. Herein, we summarized the currently resolved structure of SHARPIN as well as the emerging physiological role of SHARPIN alone or in LUBAC. Further structural and functional study of SHARPIN will provide insight into the role and underlying mechanism of SHARPIN in disease, as well as its potential application in therapeutic.